2008
DOI: 10.7705/biomedica.v28i3.72
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de conocimientos y prácticas sobre la leishmaniasis tegumentaria en un área endémica de Venezuela

Abstract: Introducción. La leishmaniasis es un grave problema de salud pública en muchas partes de América. Las poblaciones expuestas a la leishmaniasis carecen de información de la enfermedad, razón por la cual es necesario realizar intervenciones y evaluaciones educativas que contribuyan a que el control tenga un mayor impacto. Objetivo. Determinar el nivel de conocimientos y prácticas sobre la leishmaniasis tegumentaria y la fauna de flebótomos en las comunidades endémicas de Bolero Alto y Bajo del municipio Pinto Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
2
5
0
8
Order By: Relevance
“…The differences were in accordance with the published accounts of protein contents of a variety of sand fly species (7,21,38,39). Bloodmeal analysis indicated that these species were opportunistic feeders, with little attraction to a particular host species (32). Lutzomyia migonei is a widespread sand fly in South American and is a suspected Leishmania vector in several Brazilian states, as well as in Venezuela.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The differences were in accordance with the published accounts of protein contents of a variety of sand fly species (7,21,38,39). Bloodmeal analysis indicated that these species were opportunistic feeders, with little attraction to a particular host species (32). Lutzomyia migonei is a widespread sand fly in South American and is a suspected Leishmania vector in several Brazilian states, as well as in Venezuela.…”
Section: Resultssupporting
confidence: 87%
“…The current objective is to determine whether species-specific proteins occur in the saliva from two other important neotropical vectors, L. ovallesi (Ortiz) and L. migonei (França) that may affect their vectorial capacity (24)(25)(26)(27). Both species have been incriminated as vectors of cutaneous leishmaniasis in the north-central and west-central regions of Venezuela (28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…youngi is considered the primary Leishmania transmission species in Mérida State [25], although L. gomezi predominates at 300m ASL [26]. Feliciangeli [27] measured low abundance of L. gomezi in the State of Carabobo at 85 m ASL.…”
Section: Discussionmentioning
confidence: 99%
“…Los indicadores asociados al nivel de conocimiento sobre la leishmaniasis y las medidas de protección se evaluaron en los habitantes de las dos urbanizaciones mediante la aplicación de una encuesta 16 . Fueron encuestadas todas las personas mayores de siete años al momento de las visitas a las viviendas, las casas encuestadas se seleccionaron al azar.…”
Section: Indicadores Epidemiológicosunclassified
“…Se muestreó el 20% de los pobladores de cada urbanización 16 . Para determinar el nivel de conocimiento, se seleccionaron 20 preguntas del cuestionario que incluían conocimiento de la enfermedad, del vector, la transmisión y la prevención.…”
Section: Indicadores Epidemiológicosunclassified